Community-Sourced Cultural Heritage Valorization Model - Fakin Bajec, Jasna (ZRC SAZU, Založba ZRC, 2020)
Cultural practices of exploring, revitalizing, interpreting and developing cultural heritage have become an important driving force in alleviating the social, cultural, environmental and economic challenges of today's world and in initiating sustainable progress in local communities. The interpretation of cultural uniqueness is not only in the hands of professionals from heritage institutions or research centres, but also in the hands of local residents, who are recognized as heritage bearers, cultural activists, practitioners and transmitters of heritage to the younger generations. The main objective of the model is to describe steps to achieve community involvement in cultural heritage projects and guidelines for carrying out the valorisation process with the active participation of the local population. The model outlines interesting and instructive case studies of how different interactive and "soft" methods can be used to build communities by following both top-down and bottom-up approaches. In addition, presented practices also show how to convince the younger generation that local heritage offers many opportunities to put bold ideas into practice.